2002
DOI: 10.1083/jcb.200112092
|View full text |Cite
|
Sign up to set email alerts
|

ARF-GAP–mediated interaction between the ER-Golgi v-SNAREs and the COPI coat

Abstract: In eukaryotic cells, secretion is achieved by vesicular transport. Fusion of such vesicles with the correct target compartment relies on SNARE proteins on both vesicle (v-SNARE) and the target membranes (t-SNARE). At present it is not clear how v-SNAREs are incorporated into transport vesicles. Here, we show that binding of ADP-ribosylation factor (ARF)–GTPase-activating protein (GAP) to ER-Golgi v-SNAREs is an essential step for recruitment of Arf1p and coatomer, proteins that together form the COPI coat. ARF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 50 publications
6
133
1
1
Order By: Relevance
“…Previously, we reported that the ArfGAPs Glo3p and Gcs1p induce a conformational change in v-SNAREs involved in ER-Golgi and post-Golgi trafficking (Rein et al, 2002;Robinson et al, 2006). In this article, we extended these results to t-SNAREs (target-SNAREs on the target membrane) and show that Gcs1p accelerates v-t-SNARE complex formation in vitro.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…Previously, we reported that the ArfGAPs Glo3p and Gcs1p induce a conformational change in v-SNAREs involved in ER-Golgi and post-Golgi trafficking (Rein et al, 2002;Robinson et al, 2006). In this article, we extended these results to t-SNAREs (target-SNAREs on the target membrane) and show that Gcs1p accelerates v-t-SNARE complex formation in vitro.…”
Section: Introductionmentioning
confidence: 56%
“…Sec17p and Sec18p were expressed from pQE9 (QIAGEN, Valencia, CA), Sec18E350Qp was expressed from pQE30 (QIAGEN). The vectors for expression of Gcs1p, Glo3p, and Age2p and Arf1⌬N17p-Q71L have been described previously (Poon et al, 1996(Poon et al, , 1999(Poon et al, , 2001Rein et al, 2002).…”
Section: Plasmidsmentioning
confidence: 99%
See 3 more Smart Citations